Dysfunction of cecal microbiota and CutC activity in mice mediating diarrhea with kidney-yang deficiency syndrome - Guo, Mingmin; Fang, Leyao; Chen, Meili; Shen, Junxi; Tan, Zhoujin; He, Wenzhi (Frontiers in Microbiology, 2024)
Objective: Previous studies have indicated that diarrhea with kidney-yang deficiency syndrome leads to a disorder of small intestine contents and mucosal microbiota. However, the relationship of TMA-lyase (CutC) activity and TMAO with diarrhea with kidney-yang deficiency syndrome remains unexplored. Therefore, this study explores the relationship between cecal microbiota and choline TMA-lyase (CutC) activity, as well as the correlation between trimethylamine oxide (TMAO), inflammatory index, and CutC activity. Method: Twenty SPF-grade male KM mice were randomly divided into the normal group (CN) and the diarrhea model group (CD). Diarrhea mouse models were established by adenine combined with Folium sennae administration. CutC activity, TMAO, interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) levels were detected, and the cecal content microbiota was sequenced. Result: After 14 days, diarrhea occurred in the CD group. Compared with the CN group, there was no significant change in the activity of CutC in the small intestine of the CD group, while the activity of CutC in the cecum was significantly increased, and the levels of TMAO, IL-6, and TNF-α showed a significant increase. The Chao1 index, Observed_species index, Shannon index, and Simpson index all exhibited a decreasing trend. The main changes at the bacterial genus level were Alistipes, Enterorhabdus, Desulfovibrio, Bacteroides, Candidatus_Saccharimonas, and [Ruminococcus]_torques_group. The results of LEfSe analysis, random forest analysis and ROC curve analysis revealed Paludicola, Blautia, Negativibacillus, Paraprevotella, Harryflintia, Candidatus_Soleaferrea, Anaerotruncus, Oscillibacter, Colidextribacter, [Ruminococcus]_torques_group, and Bacteroides as characteristic bacteria in the CD group. Correlation analysis showed a significant negative correlation between cecal CutC activity and Ligilactobacillus, and a significant positive correlation with Negativibacillus and Paludicola. The level of TMAO was significantly positively correlated with CutC activity and IL-6. Conclusion: Diarrhea with kidney-yang deficiency syndrome significantly affects the physiological status, digestive enzyme activity, CutC activity, TMAO levels, and inflammatory response in mice. Additionally, changes in the composition and function of cecal microbiota indicate an important impact of diarrhea with kidney-yang deficiency syndrome on the host intestinal microbiota balance. The occurrence of diarrhea with kidney-yang deficiency syndrome may be associated with dysbiosis of intestinal microbiota, increased CutC activity, elevated TMAO levels, and heightened inflammatory factor levels.